Analysis on Optimal Design of Telecommunication Towers of Different Bracing System using Staad Pro Software - Mohd Shah, Hareezuddin; Norwati Jamaluddin, (Recent Trends in Civil Engineering and Built Environment, 2021)
Lattice steel communication tower is a framework construction made of galvanized steel or aluminum section with a typical height from 50m to 100m above the ground level and many type of the bracing system have been design such as XB, X, Y, YD, K and KD bracing system. This study will analysis an optimal design of the tower to reduce the cost of telecommunication lattice steel tower construction by comparing the well-practiced tower bracing type and two others bracing type which is Y-bracing and X-B bracing and the tower was subjected to the basic wind load and the self-weight of the tower. The displacement and the stress towards toward the tower was determined by using the STAAD.Pro V8i. Due to this study is focusing on the comparison of the bracing type, the properties of all 3 model were same which is by using the open section angle steel 200 x 200 x 20 for the bottom section of the tower and 150 x 150x 12 for the upper section of the tower. The MS1553:2002 was used to refer the basic wind speed and the wind load force acting towards the tower have been computed in the STAAD pro software by using the ASCE-7. As a result, The XB bracing type give a bad result for all the measurement that been compare while the K bracing type seems to be the most optimal design among the other 2 bracing type.